The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1972
DOI: 10.1161/01.res.31.3.417
|View full text |Cite
|
Sign up to set email alerts
|

Canine Mitral Complex: ULTRASTRUCTURE AND ELECTROMECHANICAL PROPERTIES

Abstract: The mitral complex is a functional entity composed of the annulus, valve leaflets, chordae, and papillary muscles. The mechanical properties of the complex are dependent on the unique structural relations of the collagen in the leaflets and chordae. In the chordae the collagen is arranged in avascular columns. These columns interdigitate between muscle fibers in the papillary muscles, and the collagen is anchored to the myofiber membrane by microfibrils. In the leaflet the chordae are continuous with the dense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
79
0

Year Published

1977
1977
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(83 citation statements)
references
References 20 publications
4
79
0
Order By: Relevance
“…3, A and D, this muscle is present at this location in the ovine anterior leaflet. The ultrastructure of this cardiac muscle is similar to that of atrial muscle (12), and, similar to LA muscle, such cells contract with electrical stim- …”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…3, A and D, this muscle is present at this location in the ovine anterior leaflet. The ultrastructure of this cardiac muscle is similar to that of atrial muscle (12), and, similar to LA muscle, such cells contract with electrical stim- …”
Section: Discussionmentioning
confidence: 70%
“…MV leaflets have extensive passive collagen fiber networks (5,11,12,15,18), and the stress-strain relationship of isolated leaflets (3,14,22,27) is consistent with the material properties of passive collagen fibers. Our recent study (21), however, suggested that leaflet stiffness in the beating heart (slope of the leaflet stress-strain curve) was much greater than that of passive tissue, and studies of freshly isolated, oxygenated, stimulated leaflets in myographs (39) and in open hearts on cardiopulmonary bypass (CBP) (7,32) have suggested that the mechanical properties of MV leaflets may be altered actively.…”
mentioning
confidence: 55%
See 3 more Smart Citations